Augmenting efl vocabulary learning and reading comprehension through mobile phone-based vocabulary learning tasks and computer-based reading activites - Imtiaz, Hassan Taj (2022)
EFL reading is a crucial input that is central to one’s academic progress, work environment, and social interactions. EFL reading is a complex process because there are many factors that play their part in successful reading experience. EFL vocabulary is one the most important factors in reading process as it provides the basis for the interaction between the text and the reader. Experts have been hard at work to devise means and ways to improve EFL reading comprehension. Since technology has permeated our lives, they have turned to technology to assist in the process of EFL reading. The use of technology in EFL reading instruction has been through two platforms: computers and mobile phones. The present study seeks to combine the affordances of these two platforms to augment EFL vocabulary learning and reading comprehension of students in Preparatory Year Programme (PYP) at a public university in the Kingdom of Saudi Arabia. It also aims to study the students’ attitude towards EFL in general and towards the combined usage of these platforms to enhance EFL reading comprehension and EFL vocabulary learning in particular. The participants were students (N = 131) divided into four preformed groups, (n = 65) male and (n = 66) female students. The study spanned a period of six weeks and had a mixed methods design. One group of males (n = 32) and one of females (n = 34) formed the control group while the other two groups of males (n = 33) and females (n = 32) were given the treatment. Research instruments used for data collection were an achievement test, two questionnaires and a semi-structured interview protocol. All data collection instruments were developed by the researcher and were piloted, for reliability and consistency. The treatment comprised of two strands that were vocabulary instruction and reading comprehension. The subjects in the treatment condition received multi glossed vocabulary through mobile phones using WhatsApp tool while computer-generated reading activities made with Hot Potatoes tool were administered in language laboratory. The control groups were taught through traditional classroom method which follows a presentation, practice and production model. Pre-test and post-test data and data from questionnaires were analysed through descriptive statistics and inferential statistics. Data from the semi-structured interviews was discussed qualitatively. Findings of the study revealed that the treatment groups outperformed their counterparts in the control groups both in vocabulary and reading comprehension components of the achievement test. Results of the questionnaire for the treatment group showed that the treatment had positive impact on attitudes and perception of the participants towards EFL reading in general and they reported positive attitudes towards the use of WhatsApp and Hot Potatoes as learning platforms. The findings also indicated that there was no statistically significant difference in the performance of male and female groups in treatment group on the basis of gender. The results of the study highlighted yet again that technology can be used as an effective assistive tool to augment vocabulary learning and to enhance reading comprehension skills of EFL learners. The findings of the study also suggested that simple computers and mobile phones can be used as learning platforms.